Round Robin Tournament and One-Factor - วิเชียรไพศาล, ธนวัฒน์; ตุ้นทัพไทย, มงคล; อุ่ยยะเสถียร, จริยา (KKU Science Journal, 2013)
In a sport tournament, each team plays with all other teams. In many two-team sports, there is a home team and an away team in each match. If the tournament has no suitable schedule, some teams will have a disadvantage. This paper constructs a suitable schedule for some sport tournaments by using 1-factorization.